The Influence Of Electronic Word Of Mouth Via Tiktok On Visit Intention To Dunia Fantasi Ancol - Inayah Nailah Harahap; Heppy Millanyani (Lembaga Teewan Journal Solutions, 2026)
The growth of TikTok as platform of social media has changed the way individuals search for or evaluate tourism-related information before making travel decisions. Electronic word of mouth (eWOM) shared through TikTok, for example user reviews, travel videos, and destination recommendations, has shifted into a crucial information source for compatible visitors. However, not all online information is automatically accepted by users, raising the question of what makes eWOM content useful enough to adopt when making decisions. This study evaluates the influence of the quality of arguments, the credibility of source, and the requirement for information on information usage, information adoption, and visit intention related to Dunia Fantasi Ancol, using the Information Adoption Model (IAM) as the theoretical framework. A quantitative approach was applied using an online questionnaire distributed to 385 TikTok accounts who had been exposed to Dufan-related eWOM content. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings are expected to deepen understanding of the way TikTok-based eWOM affects users' information evaluation and adoption before visit intention is formed. For practitioners, the results offer insights to help tourism operators improve their digital communication strategies on TikTok. Academically, this study gives a contribution to the reference regarding the implementation of IAM in the context of TikTok-based eWOM and tourism.